2017
DOI: 10.1002/pro.3189
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome destabilizes native and non‐native structures in a nascent multidomain protein

Abstract: Correct folding is a prerequisite for the biological activity of most proteins. Folding has largely been studied using in vitro refolding assays with isolated small, robustly folding proteins. A substantial fraction of all cellular proteomes is composed of multidomain proteins that are often not amenable to this approach, and their folding remains poorly understood. These large proteins likely begin to fold during their synthesis by the ribosome, a large molecular machine that translates the genetic code. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 44 publications
13
74
0
Order By: Relevance
“…This tether length is clearly longer than what is required for folding of a similar-sized Ig-like domain such as the I27 titin domain that folds at a tether length of ~35 residues, as determined by FPA and cryo-EM [3]. The simplest explanation for the long tether length required for cotranslational folding of FLN5 is that the ribosome surface destabilizes the folded state relative to the unfolded state [14], as has been observed for other proteins when tethered to a ribosome [20,35,36].…”
Section: Cotranslational Folding Of the Fln5 Domainmentioning
confidence: 99%
“…This tether length is clearly longer than what is required for folding of a similar-sized Ig-like domain such as the I27 titin domain that folds at a tether length of ~35 residues, as determined by FPA and cryo-EM [3]. The simplest explanation for the long tether length required for cotranslational folding of FLN5 is that the ribosome surface destabilizes the folded state relative to the unfolded state [14], as has been observed for other proteins when tethered to a ribosome [20,35,36].…”
Section: Cotranslational Folding Of the Fln5 Domainmentioning
confidence: 99%
“…For multidomain proteins, the vectorial nature of cotranslational folding can affect the pathway by altering which domain folds first (15,29,30). Other studies have suggested the ribosome and/or translation may alter the stable intermediates that single domains sample during folding (16,23). Here, we focus on how attachment to the ribosome changes the folding barrier (i.e., the transition state) of a single protein domain that folds without stable intermediates.…”
mentioning
confidence: 99%
“…Recent experiments harnessing the ability of the force generated by folding to release stalled nascent chains provide insight into the point during translation when different types of proteins fold (17)(18)(19)22). FRET and force spectroscopy experiments reveal the partially folded conformations some domains access before their entire sequence has left the exit tunnel (16,23). Pulse proteolysis and optical trapping experiments have been used to explore the energy landscape of RNCs outside the exit tunnel, showing that the ribosome significantly alters the stability and dynamics of proteins (13,14,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chaperones play an even more prominent role in the assembly of large multi-domain proteins, which are more prone to inter-domain misfolding events [48][49][50]. A recent study by Liu et al used optical tweezers to better to evaluate the synthesis and early folding intermediates of the multi-domain protein, EF-G, an essential mediator of ribosome mRNA translocation (as detailed in Section 1 and 2a) [49]. This study demonstrated that both the ribosome and TF help reduce any inter-domain misfolding so that the N-terminal G domain can fold efficiently.…”
Section: Forces On the Nascent Polypeptide Generated During Co-translmentioning
confidence: 99%